Satisfaction from the Actions of the Local Governments: Research Report - Alberski, Robert Paweł (Political Preferences, 2020)
In the article two main issues are depicted: the evaluation of activities of voyts, mayors and also the evaluation of local government activities. In a research conducted from the end of 2018 until the beginning of 2019 we decided to verify 3 hypotheses. First one was: confidence towards the local government results from positive evaluations of voyts and mayors activities. The results were compared with the data from previous research. The second hypothesis assumes, that positive evaluation of local government activities is not connected to the activities of single executive body, but is connected to how the whole system of local government works. Third one, however, assumes that local government on the level of voivodeship is rated lower than city (commune) government. Relatively high level of satisfaction about the activities of voyts and mayors, that were recorded in 2012 research not only remained but even increased. This is the factor that strengthens confidence in local government and favors their positive evaluation. Also voivodeship governments are positively evaluated by the surveyed, however, the level of satisfaction is lower than those of other local authorities.